Localization of preferential sites of rearrangement within the BCR gene in Philadelphia chromosome-positive acute lymphoblastic leukemia. - Denny, C T (1989)
The Philadelphia chromosome associated with acute lymphoblastic leukemia (ALL) has been linked to a hybrid BCR/ABL protein product that differs from that found in chronic myelogenous leukemia. This implies that the molecular structures of the two chromosomal translocations also differ. Localization of translocation breakpoints in Philadelphia chromosome-positive ALL has been impeded due to the only partial characterization of the BCR locus. We have isolated the entire 130-kilobase BCR genomic locus from a human cosmid library. A series of five single-copy genomic probes from the 70-kilobase first intron of BCR were used to localize rearrangements in 8 of 10 Philadelphia chromosome-positive ALLs. We have demonstrated that these breakpoints are all located at the 3' end of the intron around an unusual restriction fragment length polymorphism caused by deletion of a 1-kilobase fragment containing Alu family reiterated sequences. This clustering is unexpected in light of previous theories of rearrangement in Philadelphia chromosome-positive chronic myelogenous leukemia that would have predicted a random dispersion of breakpoints in the first intron in Philadelphia chromosome-positive ALL. The proximity of the translocation breakpoints to this constitutive deletion may indicate shared mechanisms of rearrangement or that such polymorphisms mark areas of the genome prone to recombination.